Behavioural determinants of perceived managerial and leadership effectiveness in Argentina. Issue 4 (7th August 2016) - Ruiz, Carlos E.; Hamlin, Robert G.; Carioni, Angeles
Abstract : The purpose of this empirical study was to explore the perceptions of Argentinean managers and non-managerial employees about managerial and leadership effectiveness, and the extent to which the findings are generalized to other countries. The central research question addressed was as follows: How do people employed in Argentinean companies behaviourally distinguish effective managers from ineffective managers, and to what extent are the findings culture-specific or context-general? A total of 42 employees from private and public sector organizations in Cordoba, Argentina, were interviewed using critical incident technique. The interviews generated 302 critical incidents of which 155 were examples of positive ( effective ) managerial behaviour, and 147 of negative ( ineffective ) managerial behaviour. The findings suggest that Argentineans perceive as effective those managers who are supportive, considerate, motivating, caring, good decision makers, approachable, participative, fair-minded, communicative, actively involved, and who act as role models. This challenges the widely held belief that Argentineans prefer authoritarian managers over democratic ones.